(untitled) (Journal of Parents and Teachers, 2025)
The article recounts that after the storm, calm always arrives, and after night comes day. Therefore, depression must be overcome gradually, with positivity and hope. Of course, everyone has stormy days, but one should not allow themselves to be continuously influenced by them, as this can lead to a feeling of hopelessness.